Comparison of culture- and quantitative PCR-Based indicators of antibiotic resistance in wastewater, recycled water, and tap water - Rocha, Jaqueline (2019)
Standardized methods are needed to support monitoring of antibiotic resistance in environmental samples. Culture-based methods target species of human-health relevance, while the direct quantification of antibiotic resistance genes (ARGs) measures the antibiotic resistance potential in the microbial community. This study compared measurements of tetracycline-, sulphonamide-, and cefotaxime-resistant presumptive total and fecal coliforms and presumptive enterococci versus a suite of ARGs quantified by quantitative polymerase chain reaction (qPCR) across waste-, recycled-, tap-, and freshwater. Cross-laboratory comparison of results involved measurements on samples collected and analysed in the US and Portugal. The same DNA extracts analysed in the US and Portugal produced comparable qPCR results (variation <28%), except for blaOXA-1 gene (0%–57%). Presumptive total and fecal coliforms and cefotaxime-resistant total coliforms strongly correlated with blaCTX-M and intI1 (0.725 ≤ R2 ≤ 0.762; p < 0.0001). Further, presumptive total and fecal coliforms correlated with the Escherichia coli-specific biomarkers, gadAB, and uidA, suggesting that both methods captured fecal-sourced bacteria. The genes encoding resistance to sulphonamides (sul1 and sul2) were the most abundant, followed by genes encoding resistance to tetracyclines (tet(A) and tet(O)) and β-lactams (blaOXA-1 and, blaCTX-M), which was in agreement with the culture-based enumerations. The findings can help inform future application of methods being considered for international antibiotic resistance surveillance in the environment.